2022
DOI: 10.3390/su14063183
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Pattern and Enrichment Mechanism of Selenium in Topsoil in Handan Se-Enriched Belt, North China

Abstract: Selenium (Se) is an essential trace element for human health with crucial biological functions. In this study, Se concentrations and physicochemical properties of soils in central and western Handan were determined to investigate their spatial distribution, enrichment degree, influencing factor, and geological source. The results show that: (1) Se concentrations vary from 0.00 to 1.95 μg/g, with an average of 0.45 μg/g, which exceed the mean of Se in soils in China (0.29 μg/g) and Hebei Plain (0.21 μg/g). (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…As an efficient irrigation method, water-saving drip irrigation gradually releases water into the surrounding soil through point sources, and then affects the migration of dissolved selenium in the soil. The monitoring results showed that drip irrigation could promote the vertical migration of effective selenium in the soil, especially in the close soil layer, where the selenium content increased [13]. This phenomenon may be related to the soil moisture gradient caused by dripping water, which drives the movement of the dissolved selenium.…”
Section: Influence Of Drip Irrigation Conditions On Effective Soil Se...mentioning
confidence: 97%
“…As an efficient irrigation method, water-saving drip irrigation gradually releases water into the surrounding soil through point sources, and then affects the migration of dissolved selenium in the soil. The monitoring results showed that drip irrigation could promote the vertical migration of effective selenium in the soil, especially in the close soil layer, where the selenium content increased [13]. This phenomenon may be related to the soil moisture gradient caused by dripping water, which drives the movement of the dissolved selenium.…”
Section: Influence Of Drip Irrigation Conditions On Effective Soil Se...mentioning
confidence: 97%
“…Conversely, an intake below 17 µg per day may lead to conditions such as Kashin-Beck disease [5], cardiovascular complications ( [6], or susceptibility to viral infections. With the burgeoning interest in the geochemical behaviors of Se and its biomedical functionalities, Se is garnering increasing global attention [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have demonstrated that plant absorption and enrichment of Se predominantly hinge upon the Se forms in soil [19][20][21][22][23][24][25][26][27], soil's physicochemical properties [19][20][21][22][23][24][25][26][27], and the plant's Se enrichment and absorption capabilities [19][20][21][22][23][24][25][26][27]. The principal determinant influencing Se migration within the soil-plant system is the soil's available Se content, with soil's physicochemical properties also emerging as pivotal factors influencing this availability [7][8][9][10][11][12][13][14][15][16][17][18]. Several studies have confirmed that in alkaline soils with favorable aeration conditions, Se primarily exists in the form of selenite [7][8][9][10][11][12][13]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium is an essential trace element for human health with crucial biological functions. Hao [5] showed Se concentrations and physicochemical properties of soils in China by determining their spatial distribution, enrichment degree, influencing factor, and geological source. The results show that: (1) Se concentrations vary from 0.00 to 1.95 µg/g, with an average of 0.45 µg/g, which exceed the mean of Se in soils in China (0.29 µg/g) and the Hebei Plain area (0.21 µg/g).…”
mentioning
confidence: 99%